2018
DOI: 10.1021/acs.energyfuels.8b01713
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation of the Interaction between Hydrate Formation and Wax Precipitation in Water-in-Oil Emulsions

Abstract: The study of the interaction between hydrate formation and wax precipitation in water-in-oil (W/O) emulsions is of great significance for the security of development in deep-water waxy oil and gas fields. Experiments of natural gas hydrate formation in W/O emulsions containing wax crystals were performed in a high-pressure autoclave. The macro-parametric data, including pressure, temperature, hydrate induction time, hydrate growth amount and rate, were compared and analyzed. Results indicated that the stage be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 64 publications
6
51
0
Order By: Relevance
“…They then established a viscosity model of wax hydrate slurry considering the phase interactions. Chen et al 9 carried out the hydrate formation experiments of waxy w/o systems in a high pressure reactor, and found that wax crystals had an inhibitory effect on hydrate nucleation. With the increase of wax content, the induction period of hydrate formation is prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…They then established a viscosity model of wax hydrate slurry considering the phase interactions. Chen et al 9 carried out the hydrate formation experiments of waxy w/o systems in a high pressure reactor, and found that wax crystals had an inhibitory effect on hydrate nucleation. With the increase of wax content, the induction period of hydrate formation is prolonged.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many studies have been conducted to investigate the interaction between hydrate and wax in terms of nucleation, − formation, − agglomeration, ,− deposition, , and plugging . The details and main conclusions of these studies have been discussed in our previous study and will not be repeated here.…”
Section: Introductionmentioning
confidence: 99%
“…To date, different research has been performed to study the coupling between hydrate issues and wax issues. The results of this research haves shown that wax could affect hydrate issues through affecting the nucleation, − formation, − agglomeration, ,− deposition, , and plugging processes. However, the main conclusions and mechanisms obtained from this research can be quite different and sometimes contradictory with each other.…”
Section: Introductionmentioning
confidence: 84%